Pioneirismo, disciplina e paternalismo nas relações de trabalho entre proprietário e imigrantes no século XIX : o caso da colónia de Nova Lousã, em São Paulo - Truzzi, Oswaldo; Scott, Ana Silvia Volpi (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
In 1867, João Elisário de Carvalho Monte-Negro, born in Lousã, became a farmer in Pinhal, at the hinterland of São Paulo. He called his property Nova Lousã (New Lousã) and brought to it families from his village to work as free wage labourers, in a time when slavery prevailed in Brazil. His farm succeeded and was taken as a model of free labour adoption in São Paulo. In this paper, we discuss how work was organized in Nova Lousã, and argue that paternalism and fellow countryman bonds structured the pattern of relations between rural workers and farmer in Nova Lousã.